STUDENTS’ ACHIEVEMENT IN READING COMPREHENSION DURING ONLINE CLASS - Sihombing, Efrida Irawanty (ELP (Journal of English Language Pedagogy), 2023)
This research was conducted to describe students’ achievements at the third semester of English Department students of UMMY Solok at 2021/2022 academic year in reading comprehension during online classes. The researcher found several problems in the process of learning reading comprehension through online classes, namely, some students still found it difficult and were confused to determine language features, generic structures, main ideas, and lack of concentration because sometimes the internet connection has problems. The research method used in this research was ex post facto. The population of this research was all third semester of English Department students of UMMY Solok. The sample of this research was 16 students. Samples were taken using the saturation sample technique. Then the instruments used in collecting data were students’ scores and interviews with students. The results showed that more than half of the students got final exam scores above 70. It means that almost all students got good achievements in reading comprehension during online classes, and two factors affect their achievement, namely internal and external factors. So, online classes were not as bad as students think. Even though the teaching-learning process system has changed to online classes, students can still get good achievements. It was recommended that further researchers discuss other skills to conduct similar research so that students can develop their knowledge well.